EFFECT OF GRAPHENE CONTENT ON THE MECHANICAL, PHYSICAL AND THERMAL PROPERTIES OF IMPACT MODIFIED POLY(LACTIC ACID) COMPOSITE - Zainoha Zakaria; Fatin Adilah Jamsari; Muhammad Akmal Ahmad Saidi; Azman Hassan; Wong Joon Fatt (PERINTIS eJournal, 2021)
The objective of the study is to investigate the effect of graphene content (0.5, 1.0, 1.5 and 2.0 phr) on mechanical, physical and thermal properties of impact modified PLA. Core shell rubber (CSR) at a fixed PLA:CSR ratio (95:5) was used as the impact modifier for this study. Flexural strength and modulus were reduced with addition of CSR by 11.30% and 6.65%, respectively. However, the addition of graphene showed a fluctuated trend in the flexural strength of impact modified PLA while increasing trend was observed for the flexural modulus. PLA/CSR incorporated with 1.5 phr graphene showed the highest flexural strength at 21.6 MPa. Physical properties were analyzed through water absorption test at 30℃ and 50℃ . The incorporation of CSR and graphene decreased the water absorption at both temperatures and retarded the biodegradation of PLA. Thermal properties were analyzed using thermogravimetry analysis (TGA) and differential scanning calorimetry (DSC). TGA showed that CSR decreased the thermal stability of neat PLA by 9.1% as indicated by the initial decomposition temperature (T5) and 7.3% for maximum decomposition temperature (Tmax). On the other hand, the addition of graphene into PLA/CSR increased the thermal stability of the impact modified PLA. DSC analysis showed an increase in thermal stability of PLA, as indicated by the shifting of glass transition temperature (Tg) and melting temperature (Tm) to a higher temperature. Fourier Transform Infrared Spectroscopy (FTIR) was used to identify functional group and interactions in the nanocomposites. FTIR spectra showed some interaction between PLA matrix with CSR but no interaction was observed between PLA with graphene. The overall results showed the potential of graphene/CSR/PLA nanocomposite as an advanced bio-based nanocomposite.